A Study Of The Semantic Features Of Explicit Judgements In Political Speeches In American English - Nguyễn Thanh Tâm (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
First of all, I would like to express my heartfelt gratitude to my supervisor, Dr. Ngu Thien Hung, who took his valuable time to read my manuscript and has given invaluable comments, careful correction and great encouragement for the implementation of the study. I am indebted to all my lecturers at the Department of English, Da Nang University of Foreign Languages and the Foreign Languages College of Ha Noi University for their useful lectures which set the ideas for this study. I am also deeply grateful to the staff at the library of Da Nang University of Foreign Languages who have helped me search for valuable materials to carry out the research. Also, I would like to give special thanks to my family and my friends who have given me spiritual support for accomplishing the study.